SYNTHESIZING NITRILE-CONTAINING GLYCONITRILE (CO) POLYMERS - Rakhimberlinova Zh.B.; Mustafina G.A.; Takibayeva A.T.; Kulakov I.V.; Iskakov A.R.; Nazarova O.G. (Academic Scientific Journal of Chemistry, 2019)
The article presents the results of studying the production of new nitrile-containing monomers by acylation of unsaturated N- and N,N′ - α-aminoacetonitrile chlorides (meta) acrylic acids using acrylamide. The initial unsaturated N- and N,N′ - α-aminoacetonitriles were synthesized by interaction of glycolic acid nitrile (glyconitrile) with amines of various classes. The ability of new monomers to radical (co)polymerization was studied, namely, the possibility of producing polyacrylamides based on N,N′ nitrile derivatives of (meta) acrylamide and vinyl ester (N - acetonitrile) monoetholamine (VEEAN) with acrylamide in bulk in the presence of radical initiators and organic solvents with formation of carbochain polymers. The formation of nitrile-containing polyacryamides is confirmed by the data of the elemental analysis, viscometry, IR spectroscopy. Viscometric data [ή] = 0.10 - 0.29 dl/g of polymers indicate low reactivity of the synthesized nitrile acrylamides compared to acrylamide that is associated with the steric effect of the chain length. The synthesized copolymers were studied as modifiers of urea-formaldehyde binders (UFB) used to strengthen unstable rocks. The samples strengthened with UFB solutions without a modifier showed low strength indices for 62 and 77 % concentrations, respectively, while introduction of nitrile-containing copolymers in the amount of 1-5 % wt. improved strength characteristics of the samples by 1.2-1.8 times. The good strength results for mine rocks are explained by the increased flexibility and elasticity of the urea-formaldehyde binder chains with new functional groups responsible for the resin adhesion to the rock.